Inventory and Assessment of Geoheritage in Poás Volcano National Park, Costa Rica - Dennis Pérez-Umaña (Geoconservation Research)
The number of geoconservation studies in Costa Rica has been increasing in the last 10 years. The Poás Volcano National Park has been characterized as one of the most visited places in Costa Rica where many tourists come to see one of the most emblematic volcanoes in the country and Central America. This study documents the process of recognizing five key geomorphosites of volcanic origin where Principal Crater stands out as the site with the highest overall value. Other places of interest are the Botos Cone and Von Frantzius Cone, whose proximity to the Principal Crater is a scenic attraction that many visitors take advantage of to enjoy the landscape that the volcano offers. All the geomorphosites have cultural and historical relevance as Costa Ricans have a strong sense of belonging to this volcano. The zoning of the National Park is very restrictive and protects the geomorphosites from human disturbance, which is why Public Use Zones should be used to access the geomorphosites proposed in this article. We evaluate the geomorphosites in the Poás Volcano National Park and how it has influenced the Costa Rican population, having been an inspiration for artists and scientists who developed artistic works and several studies related to this volcano.